An observational study on disturbed peripheral circadian rhythms in hemodialysis patients. (July 2015) - Russcher, Marije; Chaves, Inês; Lech, Karolina; Koch, Birgit C. P.; Nagtegaal, J. Elsbeth; Dorsman, Kira F.; Jong, Anke 't; Kayser, Manfred; van Faassen, H. (Martijn) J. R.; Kema, Ido P.; van der Horst, Gijsbertus T. J.; Gaillard, Carlo A. J. M.
<x xml:space="preserve">Abstract</x> The quality of life of hemodialysis (HD) patients is hampered by reduced nocturnal sleep quality and excessive daytime sleepiness. In addition to the sleep/wake cycle, levels of circadian biomarkers (e.g. melatonin) are disturbed in end-stage renal disease (ESRD). This suggests impaired circadian clock performance in HD patients, but the underlying mechanism is unknown. In this observational study, diurnal rhythms of sleep, serum melatonin and cortisol concentrations and clock gene mRNA expression are compared between HD patients (n = 9) and healthy control subjects (n = 9). In addition, the presence of circulating factors that might affect circadian rhythmicity is tested in vitro with cell culture experiments. Reduced sleep quality (median sleep onset latency [interquartile range] of 23.9 [17.3] min for patients versus 5.0 [10] minutes for controls, p < 0.01; mean (± SD) sleep efficiency 70.2 ± 8.1% versus 82.9 ± 10.9%, p = 0.02 and mean awake minutes after sleep onset 104.8 ± 27.9 versus 54.6 ± 41.6 minutes, p = 0.01) and increased daytime sleepiness (mean Epworth Sleepiness Score of 10.0 ± 4.8 versus 3.9 ± 2.0, p < 0.01) were confirmed in HD patients. Reduced nocturnal melatonin concentrations (1 AM: 98.1 [122.9] pmol/L versus 12.5 [44.2] pmol/L, p = 0.019; 5 AM: 114.0 [131.6] pmol/L versus 11.8 [86.8] pmol/L, p = 0.031) and affected circadian control of cortisol rhythm and circadian expression of the clock gene REV-ERBα were found. HD patient serum had a higher capacity to synchronize cells in vitro, suggesting an accumulated level of clock resetting compounds in HD patients. These compounds were not cleared by hemodialysis treatment or related to frequently used medications. In conclusion, the abovementioned results strongly suggest a disturbance in circadian timekeeping in peripheral tissues of HD patients. Accumulation of clock resetting compounds possibly contributes to this. Future studies are needed for a better mechanistic understanding of the interaction between renal failure and perturbation of the circadian clock.